The Production of Solid and Liquid Organic Fertilizers From Cow and Goat Manure and Their Application to Corn Crops - Roziq, Ahmad; Shulthoni, Moch.; Piluharto, Bambang; Afif Difa Asy Syafiq, Muhammad; Ilma Ahmad, Zakiyyah (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
Bangsri is a village in the Plandaan Sub-district, Jombang Regency, East Java Province, where most residents live as farmers. In Bangsri, several farmers and breeders have over 500 goats and sheep. However, they face challenges in processing goat manure into solid and liquid organic fertilizers that would be more beneficial for plants. Currently, goat farmers lack the innovation to process the manure, often just piling it up or discarding it. Additionally, the sharecropping system in agriculture is becoming increasingly unprofitable, and crop yields are suboptimal, particularly during the dry season, due to high processing costs. As a result, many rice fields are abandoned by their owners. The way to overcome this problem is through a service-learning approach. In service activities, the team provides training and assistance in making organic fertilizer to provide added value for farmers and breeders. As a result, farmers and breeders have started implementing the techniques learned in the training to produce both solid and liquid organic fertilizers. This initiative has been positively received in Bangsri Village, with noticeable improvements in crop yields